A Dynamic Model for Effective and Optimal Planning of Formwork in Construction Projects - Renata Baskova; Alena Tazikova; Zuzana Strukova; Maria Kozlovska; Jozef Cabala (Buildings, 2023)
The cost of producing one cubic meter of concrete structure, depending on the structure’s shape, type, and complexity, can be variously high. The cost of concrete, reinforcement, formwork, and labor ratio varies. But unlike the cost of concrete and reinforcement, which tend to be similar in the terms of the conditions of a particular construction project, the cost of formwork and work with it are different for different contractors. It often depends on the appropriateness of the formwork system used, the optimal placement of the formwork sets, the minimization of downtime, and the efficiency of the carpenters’ work. Formwork modeling in the construction preparation phase intervenes in this planning area, where construction sources are defined and quantified, and the time course of their deployment is determined. The current paper deals with optimizing formwork selection and deployment in concrete structure execution. Even if several requirements must be considered when selecting and modeling the formwork (e.g., construction time, quality of concrete structure, etc.), an effort to minimize the cost of formwork, and thus construction cost, plays the most significant role. A dynamic model for effective and optimal planning of formwork in construction projects, including formwork cost analysis, is presented in the paper. The included case study demonstrated the planning of the formwork through a software application developed based on the computational algorithm of the dynamic model presented. A case study is presented in the article as a research method. An office building with five above-ground floors and one underground floor was chosen for the case study. To solve the case study, the formwork for horizontal structures (i.e., beams and slabs) is considered. The goal of the case study is to identify research questions and apply time and cost optimization to a selected specific building.